Analisis Aspek Leksikal pada Kosa Kata “Rabb, Malik, dan Ilah” dalam Surah An-nās Ayat 1-3 (Kajian Stilistika) - Pranata, Robby (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Stylistics is a branch of linguistics that studies variations and styles of language use to convey meaning, aesthetic effects, and certain communicative purposes. In classification, stylistics is a branch of macrolinguistics, which is the science that studies language in relation to external factors. Stylistics consists of several sub-branches, one of which is the lexical element, which is a stylistic study that focuses on word choice (diction). This analysis aims to identify the aspects of lexical stylistics in the vocabulary of Rabb, Malik, and Ilah in Surah An-Nās verses 1-3. The aspects of lexical stylistics analyzed consist of three things: word choice, synonymic relations, and the intensity of meaning in the context of the verses. This analysis uses a qualitative method with a type of research known as library research (literature study), which involves collecting data from books, journals, and other literature related to stylistics using the Qur’an as the main source. In the analysis process, this qualitative approach is chosen because this research focuses on the interpretation of meaning, not on quantitative measurement. As a result, the lexical stylistic approach to the vocabulary analyzed not only reveals understanding from a linguistic perspective but also strengthens the intensity of meaning contextually. This study shows that the lexical arrangement in Surah An-Nās verses 1-3 has a meaningful order that reflects the perfection of the structure of the language of the Qur’an. Keywords: Lexical stylistics, Linguistics, Surah An-Nās.